Language Enhancement Activities in the EFL Interpreting Classroom: A Cognitive Approach Proposal to Mitigate Omissions and Grammatical Errors - Rakhmawati, Susi Septaviana; Emilia, Emi; Rodliyah, Rojab Siti (Journal of Foreign Language Teaching and Learning, 2026)
Background: Language enhancement activities (LEAs) are among targeted pedagogical intervention which can be proposed in developing critical skills of simultaneous interpreting among beginner trainee to address any cognitive-linguistic constrains causing common interpreting errors. As a cognitively demanding task, simultaneous interpreting can be demanding for Indonesian undergraduate students learning English as a Foreign Language who must manage both interpreting subskils and B language (English) proficiency simultaneously. Objective: This research investigates the predominant error profiles of Indonesian interpreter trainees, maps these errors to cognitive effort imbalances using Gile's (2009) Effort Model and Gravitational Model, and proposes a Reflective LEA Framework to mitigate comprehension omissions and grammatical errors in bidirectional interpreting tasks. Methods: A qualitative case study within an action-research framework was conducted over 14 weeks. Twelve stratified undergraduate students were selected from a class of 24 to ensure diverse performance representation. A total of 200 errors from transcribed SI performances of two authentic speeches were analyzed using an integrated coding scheme combining Barik's (1971) omission typology and Gile's (2011) Errors, Omissions, and Infelicities framework. Student questionnaires provided qualitative data on perceived cognitive effort and LEA effectiveness. Findings: Comprehension omissions were the most frequent error type, predominantly in B→A (English-to-Indonesian) interpreting, indicating Listening Effort (L) overload. Grammatical errors were concentrated in A→B (Indonesian-to-English) interpreting, reflecting Production Effort (P) deficits arising from L1 interference such as, copula deletion, article omission, tense inconsistency. Authentic, contextualized LEAs received significantly higher student effectiveness ratings than decontextualized drills. Conclusion: The study proposed a reflective LEA framework grounded in the Cognitive Effort Model and Gile's Gravitational Model, integrating directionality-aware activities within a cyclical diagnostic-intervention-evaluation structure. The framework offers a practical model for integrating language enhancement into undergraduate EFL interpreter training curricula.